(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
Historically and contemporarily, immigration laws have disproportionately affected immigrant faculty and students of color because they often inadvertently function as racial policy. (Critical) legal literacy enacted via a bottom-up approach can help to address such laws. Higher education institutions, organizations, labor unions and associations are uniquely positioned to use critical legal literacy as a tool of advocacy for immigrant faculty and students of color amidst the adverse effects of COVID-19.